Eyewitnesses who engage in immediate recall are not perceived as more credible - Deck, Sarah L. (Psychology, crime & law, 2022)
Contemporaneous notes refer to witness accounts composed during or immediately after a critical event. Although contemporaneous notes can improve eyewitness accuracy, their influence upon juror decision making is unknown. This experiment was the first to investigate the effect of contemporaneous notes upon juror decision making. Mock-jurors were given a trial transcript in which the primary eyewitness read a contemporaneous note they had composed after observing an accident. The witness was either consistent with their note upon further questioning, or was inconsistent with their note. When the witness was inconsistent with their note, their testimony at trial contained critical information that was not included in their contemporaneous note. Alternatively, some participants read a trial transcript in which no contemporaneous note was presented. The witness who was inconsistent with their note was perceived as less credible than a witness who was consistent with their note, or did not present a note at trial. Moreover, the defendant was perceived as less guilty when the eyewitness was inconsistent with their note, compared to when no contemporaneous note was present. These results have important implications for the use of contemporaneous notes in legal proceedings.